Associations of Atrial Fibrillation Patterns With Mortality and Cardiovascular Events: Implications of the MISOAC-AF Trial. (7th January 2022) - Baroutidou, Amalia; Kartas, Anastasios; Samaras, Athanasios; Papazoglou, Andreas S.; Vrana, Eleni; Moysidis, Dimitrios V.; Akrivos, Evangelos; Papanastasiou, Anastasios; Vouloagkas, Ioannis; Botis, Michail; Liampas, Evangelos; Karagiannidis, Artemios G.; et al.
Aim: This retrospective cohort study aimed to evaluate the prognostic implications of the distinct atrial fibrillation (AF) temporal patterns: first diagnosed, paroxysmal, and persistent or permanent AF. Methods: In this post hoc analysis of the MISOAC-AF trial (NCT02941978), a total of 1052 patients with AF (median age 76 years), discharged from the cardiology ward between 2015 and 2018, were analyzed. Kaplan-Meier and Cox-regression analyses were performed to compare the primary outcome of all-cause mortality, the secondary outcomes of stroke, major bleeding and the composite outcome of cardiovascular (CV) mortality or hospitalization among AF patterns. Results: Of patients, 121 (11.2%) had first diagnosed, 356 (33%) paroxysmal, and 575 (53.2%) persistent or permanent AF. During a median follow-up of 31 months (interquartile range 10 to 52 months), 37.3% of patients died. Compared with paroxysmal AF, patients with persistent or permanent AF had higher mortality rates (adjusted hazard ratio (aHR), 1.37; 95% confidence interval [CI], 1.08-1.74, P = .009), but similar CV mortality or hospitalization rates (aHR, 1.09; 95% CI, 0.91-1.31, P = .35). Compared with first diagnosed AF, patients with persistent or permanent AF had similar mortality (aHR, 1.26; 95% CI, 0.87-1.82, P = .24), but higher CV mortality or hospitalization rates (aHR, 1.35; 95% CI, 1.01-1.8, P = .04). Stroke and major bleeding events did not differ across AF patterns (all P > .05). Conclusions: In conclusion, in recently hospitalized patients with comorbid AF, the presence of persistent or permanent AF was associated with a higher incidence of mortality and morbidity compared with paroxysmal and first diagnosed AF.